The Evaluasi Pemanfaatan Limbah Cair Tahu Terfermentasi sebagai Media Kultivasi Chlorella sp: Indonesia - nur rohmah, Siti; Imanulhaq, Mochammad Riziq; Aulia, Diani; Irawan, Muhammad Reza Putra; Ikhwan, Misbakhul; Abdullah, Burhanudin; Simangungsong, Tohap (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Fermented tofu wastewater is one type of organic waste that has the potential to be used as an alternative nutrient source in microalgae cultures, including Chlorella sp., This study aims to evaluate the use of fermented tofu wastewater as a culture medium for Chlorella sp., by comparing the growth rate at several treatment concentrations (15, 20, and 25 mg/L) and two controls, namely non-fermented wastewater and commercial NPK fertilizer. The study used a completely randomized design (CRD) with three replicates and was conducted over 14 days. The parameters observed included daily cell density and water quality (pH and temperature). The results showed that all treatments, including the controls, produced relatively similar growth patterns, with peak density occurring on days 9 to 10. Based on the Kruskal–Wallis test, there were no significant differences between treatments (p>0.05), indicating that variations in fermented tofu liquid waste concentration in the range of 15–25 mg/L did not have a significant effect on the growth of Chlorella sp., Water quality during maintenance was within the optimal range, with a temperature of 25.2–26.0 °C and a pH of 8.6–9.3. These findings indicate that fermented tofu liquid waste has the potential as an alternative medium for microalgae culture, but optimization of the concentration or modification of the treatment is needed to obtain a significant increase in growth